Corporate Social Responsibility dan Leverage terhadap Harga Saham: Peran Moderasi Profitabilitas pada Perusahaan Farmasi - Sri Sapto Darmawati; Sudaryono Sudaryono; Mujiyani Mujiyani; Dio Fasha (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and Debt to Equity Ratio (DER) on stock prices and to examine the ability of Earnings Per Share (EPS) to moderate the relationship between CSR, DER, and stock prices in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research is motivated by the fluctuations in pharmaceutical companies' stock prices in the post-pandemic era and the inconsistent findings of previous studies regarding the factors influencing stock prices. Therefore, this study is expected to provide empirical evidence concerning the influence of both financial and non-financial factors on corporate stock prices. The research employs a quantitative method with an associative approach. The population consists of all pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using a purposive sampling technique, resulting in companies that met the established research criteria. The data used are secondary data obtained from annual reports and financial statements. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) to test the moderating effect of EPS. The results indicate that CSR and DER do not have a significant partial effect on stock prices. Meanwhile, EPS is proven to moderate the effect of CSR on stock prices, indicating that the influence of CSR becomes stronger in companies with higher EPS levels. However, EPS is not able to moderate the effect of DER on stock prices. These findings suggest that investors place greater emphasis on a company’s ability to generate earnings rather than on CSR disclosure levels and capital structure when evaluating stock prices. This study provides an empirical contribution by integrating non-financial and financial factors in explaining the stock prices of pharmaceutical sub-sector companies, while also extending the literature on the role of profitability as a moderating variable in the relationship between Corporate Social Responsibility, leverage, and stock prices.